Perceived Supervisor Support and Academic Procrastination in Postgraduate Students: Roles of Basic Psychological Needs Satisfaction and Learning Engagement - Lumeng Wang; Guoxia Wang (Behavioral Sciences)
Academic procrastination is a common problem among postgraduate students, one that has caused negative consequences that cannot be ignored. Therefore, finding out how to effectively eliminate academic procrastination behavior has become an essential task in educational practice. Based on the use of Self-Determination Theory (SDT) to explore the relationship between the perceived supervisor support and academic procrastination of postgraduate students, a total of 448 questionnaires were gathered from postgraduate students across China. The results showed significant correlations between the perceived supervisor support, basic psychological needs satisfaction, learning engagement, and academic procrastination of postgraduate students. The relationship between the perceived supervisor support and academic procrastination of postgraduate students was mediated by basic psychological needs satisfaction and learning engagement. Additionally, basic psychological needs satisfaction and learning engagement played a chain-mediating role between the perceived supervisor support and academic procrastination of postgraduate students. The findings of this study contributed to the enhancement of the interaction between supervisors and students in higher education and improving the quality of postgraduate education.